RNA polymerase II subunit RPB3 is an essential component of the mRNA transcription apparatus. - Kolodziej, P (1989)
To improve our understanding of RNA polymerase II, the gene that encodes its third-largest subunit, RPB3, was isolated from a lambda gt11 DNA library by using antibody probes. The RPB3 DNA sequence predicts a 318-amino-acid protein whose sequence was confirmed, in part, by microsequence analysis of the gel-purified RNA polymerase II subunit. RPB3 was found to be an essential single-copy gene that is tightly linked to HIS6 on chromosome IX. An RPB3 temperature-sensitive mutant that arrested growth after three to four generations at the restrictive temperature was isolated. When the mutant was shifted to the restrictive temperature, RNA polymerase II could no longer assemble, previously assembled functional enzyme was depleted, and mRNA levels were consequently reduced. These results demonstrate that RPB3 is an essential component of the mRNA transcription apparatus. Finally, the RPB3 protein is similar in sequence and length to RPC5, a subunit common to RNA polymerases I and III, suggesting that these subunits may play similar roles in RNA polymerases I, II, and III.